Fault location algotithm based on ann for single line-to-ground fault in MV distribution system - Abdalgane, Ali Adil (School of Electrical System Engineering, 2016)
The objectives of this project are design a typical MV network using Electro Magnetic Transient Program (EMTP/ATP); simulate a single line to ground fault in medium voltage (MV) network and analyze a captured earth fault signal using signal processing techniques; develop a fault location algorithm of single line to ground fault in medium voltage (MV) network based on ANN method; generate a Simulink circuit based on developed ANN model to locate the actual fault location.